PENERAPAN MODEL LOGICAL FRAME WORKS PROGRAM PEMBERDAYAAN LANSIA DI KECAMATAN KARANGANYAR KABUPATEN PEKALONGAN - Yuniarti Yuniarti (Pena Jurnal Ilmu Pengetahuan Dan Teknologi, 2015)
The  Population    of  the  old  ages  in  year  2020  is  projected  at  11,34%  with  a  life expectancy reaches 71,1 years olds. It will be a great problem in national development  if not taken  seriously.  This  situation  encourages  empowerment  programs  achieving  welfare  for  old age physically, mentally, socially and spiritually based promotive and preventive efforts.  It’s an  exploratory  research  with  a  qualitative  approach.  This  study  integrate  health    project /program  by  implementing  logical  frame  works.  The  study  conducted  in  the  village  Kutosari Karanganyar District of Pekalongan. Target of this study are 161 old ages over 60 years olds.  The empowerment program for old ages was compiled using Logical Frame Works model. It’s an analytical tool that provides technical instructions a health project/program. Logical Frame Works contains stakeholder analysis, problem analysis and objective analysis.  Logical Frame Works analysis result in the form of logframe matrix includes a combination of vertical logic and horizontal logic. Empowerment program for old ages contains activities that are oriented towards  healthy  behaviour,  early  detection  of  disease,  treatment  of  minor  ailment  and rehabilitative efforts. These activities included medical, psychosocial and educational services. Logical  Frame  Works  effectively  compose  of  planning  and  evaluating  the  empowerment programs for old ages. This empowerment based a promotive-preventive health behavior and early  detection  of  health  problems.  That  program  aims  achieving  welfare  for  old  ages according Law Number 13th of 1998.       Composing Logical Frame Works oriented to social and cultural aspects as well as the caracteristics of the local community for achieving optimal results.  The  empowerment  programs  for  old  ages  implemented  in  harmony  with  elderly- friendly paradigm with elderly as a subject of the programs.